Triangles and Squares for a Unique Molecular Crystal Structure: Unsupported Two‐Coordinate Lithium Cations and CC Agostic Interactions in Cyclopropyllithium Derivatives. (21st December 2017) - Dufrois, Quentin; Daran, Jean‐Claude; Vendier, Laure; Dinoi, Chiara; Etienne, Michel
Abstract: Understanding and controlling the aggregation state is germane to alkyllithium chemistry. Lewis base‐free alkyllithium compounds normally form tetrahedral tetramers or octahedral hexamers in the solid state with the lithium cations being three‐coordinate. We report that the unsupported cyclopropyl derivative 1‐(trimethylsilyl)cyclopropyllithium [μ‐ c ‐C(SiMe3 )C2 H4 Li]4 (1 ), synthesized by the reduction of 1‐(phenylthio)‐1‐(trimethylsilyl)cyclopropane, crystallizes as a tetramer in the space group I‐4 with the two‐coordinate lithium atoms forming a square. CC agostic interactions complete the coordination sphere around each lithium. The aggregate is preserved in hydrocarbon solution. Furthermore, CC agostic interactions compete intra‐ and intermolecularly with Lewis base donation as in the unsaturated dimer of 1‐(phenylthio)cyclopropyllithium [Li(thf)2 μ‐ c ‐C(SPh)C2 H4 2 Li (thf)] (3 ) which is also fully characterized.